HOW TO ADAPT STUDENTS TO SPEAKING SKILLS - Kurbanbaev, Djavod Aminbaevich; Seytniyazova , Guljakhan Mirzagalievna (Educational Research in Universal Sciences, 2023)
This article provides practical strategies for adapting students to develop strong speaking skills. The importance of identifying individual strengths and weaknesses and tailor instruction accordingly is discussed. Exercises and activities are provided to build key speaking competencies, such as vocal projection, articulation, and persuasive reasoning. Additionally, challenges that students may face in real-world settings, such as public speaking anxiety, are explored, and tips for managing these issues are provided. By incorporating these techniques into their teaching practices, educators can help students become confident and articulate communicators, enabling them to succeed both inside and outside the classroom.